1995
DOI: 10.1038/eye.1995.66
|View full text |Cite
|
Sign up to set email alerts
|

Pupil dilatation in the pseudoexfoliation syndrome

Abstract: We studied the pupil dilatation of patients with pseudoexfoliation, normals, diabetics and patients with chronic open angle glaucoma to establish whether there was a significant difference in the mydriasis achieved with cyclopentolate and phenylephrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
3
4
0
1
Order By: Relevance
“…This was in agreement with other studies showing eyes with PXS to have significantly more poorly dilating pupils compared to those with POAG and diabetes [5] [37]. This is as a result of infiltration of iris stroma with excessive extracellular matrix, causing mechanical obstruction of the dilator muscles during mydriasis [41]. Furthermore, histological studies have shown the presence of fibrotic disorganized or degenerative muscle tissue in most PXS and PXG specimens and not in controls [5] [42].…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with other studies showing eyes with PXS to have significantly more poorly dilating pupils compared to those with POAG and diabetes [5] [37]. This is as a result of infiltration of iris stroma with excessive extracellular matrix, causing mechanical obstruction of the dilator muscles during mydriasis [41]. Furthermore, histological studies have shown the presence of fibrotic disorganized or degenerative muscle tissue in most PXS and PXG specimens and not in controls [5] [42].…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of the dilator muscle in 3 cases suggests that the iris muscles may be affected early in the PEX process. The accumulation of abnormal extracellular matrix, including PEX material, and the atrophic changes of dilator muscle cells may account for poor pupillary dilation, which is characteristic of eyes with manifest PEX syndrome 25,26 but can also be observed to a minor degree in contralateral eyes. Thus, the histopathologic findings of this study indicate a bilateral, but asymmetric, compromise of the pupillomotoric function as an early manifestation of PEX syndrome.…”
Section: Commentmentioning
confidence: 99%
“…Patients with XFS have significantly smaller pupils after pharmacological dilation than persons without XFS or diabetes or individuals with primary open-angle glaucoma (POAG) (Carpel 1988;Watson et al 1995). This could be attributed to iris stiffening from exfoliation material in the stroma, sphincter muscle fibrosis and ⁄ or posterior synechiae.…”
Section: Introductionmentioning
confidence: 99%